Age and growth of the European eel [i]Anguilla anguilla[/i] in the Camargue lagoons - Melia, Paco; Bevacqua, Danièle; Crivelli, Alain Jean; De Leo, Giulio Alessandro; Panfili, Jacques; Gatto, Marino (HAL CCSD, 2006)
Age and total length (LT) data from a 11 year monitoring of the[i] Anguilla anguilla[/i] eel population of the Camargue lagoons (Rhoˆ ne delta, southern France) were collected for glass, yellow and silver eels. Three distinct models were calibrated to describe the growth process of undifferentiated eels, females and males, respectively. Uncertainty of parameter estimates was evaluated by bootstrapping. Females were characterized by larger asymptotic body size (LT) than males (580 _ 50 v. 388 _ 13 mm) and faster growth, whilst the Brody growth coefficient was larger for males than for females (means _ S.D. 3_00 10_3 _ 1_68 10_3 v. 1_73 10_3 _ 0_50 10_3). Sexual differentiation was estimated to begin at 204 _ 38 mm mean _ S.D., i.e. at the end of the second year in the lagoons, well before the LT at which macroscopic differentiation became possible (c. 300 mm). Males probably leave the lagoon or die (due to either natural or fishing mortality) within the first 3 years, whilst females can remain up to 5 years. Sexual differentiation and maturation have a major role in shaping the LT structure of the population. The LT and mass (M) data were fitted by allometric curves M ¼ aLT _ b_. The calibration of distinct curves for data from different years indicated that the allometric coefficient a was subject to wider interannual fluctuations than the allometric exponent b. A negative correlation linked the average LT and the allometric exponent (r ¼ _0_58, P < 0_01).